Strategi Pengembangan Usaha Benih Padi Bersertifikat di CV. Putra Remaja Kimia Kabupaten Karawang - Muhammad Rizki Dafa; Wagiono Wagiono; Luthfi Nur’azkiya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Karawang Regency is one area that produces high rice production in West Java.The availability of approved rice seed breeding is crucial when considering this potential, particularly to fulfill the high demand for rice production in Karawang Regency. For instance, C.V Putra Remaja Kimia, a grade A business that is under the direct supervision of BPSB, is one of the accredited rice seed breeders in West Java. However, there are difficulties in company development such as Low Quality of human resources, items that cannot be kept for an extended period, a lack of a website, a lack of advertising of certified seed products, and farmers' lack of interest in and understanding of utilizing certified seeds.This study aims to determine the results of internal and external factors in the development of certified rice seed businesses and what strategies are suitable for business development. The research method used is descriptive with quantitative and qualitative approaches. The selection of locations is made intentionally (purposive). The sample used consisted of 17 people, and the results showed that the strengths of the business were greater than the weaknesses indicated by the IFAS value of 3.25 and the calculation of EFAS obtained a value of 3.17, indicating that the certified rice seed business was greater than the opportunities of the threat..